2010
DOI: 10.1186/1743-8977-7-16
|View full text |Cite|
|
Sign up to set email alerts
|

Effects of prenatal exposure to surface-coated nanosized titanium dioxide (UV-Titan). A study in mice

Abstract: BackgroundEngineered nanoparticles are smaller than 100 nm and designed to improve or achieve new physico-chemical properties. Consequently, also toxicological properties may change compared to the parent compound. We examined developmental and neurobehavioral effects following maternal exposure to a nanoparticulate UV-filter (UV-titan L181).MethodsTime-mated mice (C57BL/6BomTac) were exposed by inhalation 1h/day to 42 mg/m3 aerosolized powder (1.7·106 n/cm3; peak-size: 97 nm) on gestation days 8-18. Endpoints… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
211
0
4

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 188 publications
(230 citation statements)
references
References 35 publications
15
211
0
4
Order By: Relevance
“…In fact, TNPs were shown to be transferred from pregnant mice to their pups [70][71][72][73]. When pregnant mice were treated with TNPs via subcutaneous injection, the genital and cranial nerve systems of the male offspring were affected [70].…”
Section: Developmental Toxicitymentioning
confidence: 99%
See 2 more Smart Citations
“…In fact, TNPs were shown to be transferred from pregnant mice to their pups [70][71][72][73]. When pregnant mice were treated with TNPs via subcutaneous injection, the genital and cranial nerve systems of the male offspring were affected [70].…”
Section: Developmental Toxicitymentioning
confidence: 99%
“…When pregnant mice were treated with TNPs via subcutaneous injection, the genital and cranial nerve systems of the male offspring were affected [70]. When time-mated female mice were treated with TNPs, their offspring showed moderate neurobehavioral alterations, although cognitive function was not affected [71]. This finding can be explained by changes in the expression of genes associated with CNS development and function [72].…”
Section: Developmental Toxicitymentioning
confidence: 99%
See 1 more Smart Citation
“…However King-Heiden et al (2009) observed QD induced necrosis and yolk sac and tail malformation, which were not characteristic to Cd 2+ evoked effects, indicating that nanostructure exhibits new qualities that are not prominent in their components. Hougaard et al (2010) observed adverse effects on neurobehavior and fertility of the offspring's of TiO 2 exposed rats. The research highlighted that the maternal NP exposure can lead to indirect effects on embryogenesis without NP accumulation in the fetus.…”
Section: Effects Of Nanoparticles On Embryogenesismentioning
confidence: 91%
“…Potential effects on the lungs include damage to membranes, cytotoxicity, genotoxicity, apoptosis (induced programmed cell death), necrosis (cell death due to toxic interference with vital cell functions), inflammation, fibrosis, and cancer [1-3, and references therein]. Inhaled nanoparticles may penetrate the alveolar-capillary barrier between the respiratory and circulatory system, and thus be translocated from the lungs [2,3,[30][31][32][33][34][35][36][37][38][39][40][41][42], and references therein]. When the nanoparticles translocate to the circulatory system, other organs may also be affected [1-3, 15, 16, 30-32, 39-42].…”
Section: Determinants Of Human Inhalation Hazards Of Persistent Enginmentioning
confidence: 99%